2010
DOI: 10.1183/09031936.00024210
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide in bronchoalveolar lavage is not diagnostic forPseudomonas aeruginosain children with cystic fibrosis

Abstract: Early detection of the cyanobacterium Pseudomonas aeruginosa in the lungs of young children with cystic fibrosis (CF) is considered the key to delaying chronic pulmonary disease. We investigated whether cyanide in bronchoalveolar lavage (BAL) fluid could be used as an early diagnostic biomarker of infection.Cyanide was measured in 226 BAL samples (36 P. aeruginosa infected) obtained from 96 infants and young children with CF participating in an early surveillance programme involving annual BAL.Cyanide was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…Regarding phenotype, previous studies have reported higher cyanide production by mucoid P. aeruginosa cultures [20,27]. Our data suggest the opposite, with nonmucoid cultures having higher HCN concentrations.…”
Section: Respiratory Infections Fj Gilchrist Et Alcontrasting
confidence: 43%
See 2 more Smart Citations
“…Regarding phenotype, previous studies have reported higher cyanide production by mucoid P. aeruginosa cultures [20,27]. Our data suggest the opposite, with nonmucoid cultures having higher HCN concentrations.…”
Section: Respiratory Infections Fj Gilchrist Et Alcontrasting
confidence: 43%
“…This is supported in vitro by reports of leukocytes challenged with Staphylococcus epidermidis producing HCN [25,26] and a recent study from the Australian Respiratory Early Surveillance Team for Cystic Fibrosis (AREST CF) team who found the neutrophil number in bronchoalveolar lavage (BAL) samples to be a predictor of cyanide concentration [27]. However, BAL neutrophil count is significantly higher in patients infected with P. aeruginosa compared with those with no infection or infection with other organisms [28] and previous studies have not identified cyanide in patients infected with organisms other than P. aeruginosa [13][14][15].…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In the current issue of the European Respiratory Journal, STUTZ et al [24] have once again shown that cyanide is increased in relation to P. aeruginosa infection in children with CF. However, they also found increased levels of cyanide in children apparently uninfected with the organism and their results suggest that the differences between the two groups of patients were too small to be of value in the individual patient to use cyanide as a marker for the early detection/presence of P. aeruginosa.…”
mentioning
confidence: 99%
“…HCN is volatile and its usefulness as a surrogate marker for the diagnosis of P. aeruginosa infection in children who cannot expectorate sputum is currently being investigated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%